1982
DOI: 10.1103/physrevb.25.4431
|View full text |Cite
|
Sign up to set email alerts
|

Raman photoselection and conjugation-length dispersion in conjugated polymer solutions

Abstract: Resonance Raman scattering (RRS) in conjugated polydiacetylene solutions is employed in order to determine the vibrational spectra of resonance-selected chromophores within a single conformationally disordered polymer chain. Although the polymer-chain length contains up to 1000 repeat units, the conjugation length (i.e, , the length over which backbone planarity is maintained without interruption and which defines the chromophore) may be as smail as three units. Variation of the solvent system can increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 14 publications
3
52
0
Order By: Relevance
“…S4). This similarity in spectral form strongly suggests that the narrow lines observed over such a broad spectral range arise from isolated chromophores (38). Because narrow single-chromophore zero-phonon lines are observed as far to the red as 680 nm, we conclude that the high-energy side of the bulk spectrum (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…S4). This similarity in spectral form strongly suggests that the narrow lines observed over such a broad spectral range arise from isolated chromophores (38). Because narrow single-chromophore zero-phonon lines are observed as far to the red as 680 nm, we conclude that the high-energy side of the bulk spectrum (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Nevertheless, conventional incremental materials development risks being impeded by lack of a robust understanding of primary photoexcitations in these systems. Is the primary photophysics of polythiophenes dominated by intermolecular interactions and H-aggregate species, or does the material actually adhere to the established concepts (36,38,41) of intrachain chromophores as derived from a wide range of compounds? Our single-molecule experiments tend to favor the latter notion, while leaving room for features of H-aggregation or other bulk solvation effects in In Zeonex, multiple chromophores emit, leading to only a 20% dip in photodetector coincidence rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, this indicates that even in samples with no chemical defects, the polymers are disordered into collections of chains with relatively short conjugated segments. 20,21,27,28 We recently demonstrated that cooling overcomes at least some of this disorder and that the temperature dependence of the spectra is consistent with relatively small barriers for twisting about the carbon-carbon single bonds. 19 Room temperature solution spectra of shorter polyenes and carotenoids (N ) 5-15), on the other hand, tend to be vibronically resolved and show smaller red shifts upon cooling.…”
Section: U + Transitions In Di-tert-butyl Polyenes and Polyene Oligomersmentioning
confidence: 99%
“…For example, ν(CdC) shows a 1/N dependence with a long polyene limit of 1440 cm -1 . [26][27][28] In low-resolution spectra, vibronic combinations of ν(C-C) and ν(CdC) coalesce into progressions of what appears to be a single, intermediate frequency of 1300-1400 cm -1 . For example, the absorption spectrum of the N ) 5 oligomer shows vibronic intervals of ∼1400 cm -1 (Figure 3).…”
Section: Hplc Analysis and Purification Of Oligomersmentioning
confidence: 99%